The outbreak of the SARS‐CoV‐2 Omicron variant make imperative the adoption of telerehabilitation in the Bulgarian health care system - Jannis Papathanasiou; Yana Kashilska; Hristo Bozov; Ivo Petrov; Stefano Masiero (PAGEPress Publications, 2022)
The rapid spread of the highly contagious Omicron variant of SARS-CoV-2 globally will challenge the accessibility and the delivery of physical and rehabilitation medicine (PRM) services. Many health care systems throughout the world performed effective reforms such as the transition to telerehabilitation (TR). In Bulgaria, TR is still not regulated by law, and terms such as teleconsultation and tele-education have not yet been introduced. The adoption of TR in the Bulgarian health care system will undoubtedly increase the accessibility to rehabilitation treatment for a larger group of Bulgarian patients with various neurological, cardiorespiratory, musculoskeletal, and oncological conditions and will significantly contribute to the PRM services modernization in Bulgaria.